2018
DOI: 10.13189/ujer.2018.060416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Justice Behaviors on Organizational Silence and Cynicism: A Research on Academics from Schools of Physical Education and Sports

Abstract: In this research, it is aimed to examine the effect of organizational justice behaviors on organizational silence and cynicism based on the opinions of academics who serve in Schools of Physical Education and Sports, and Faculties of Sports Sciences. Research group consisted of academics from 22 different universities in Turkey. There are 320 people (245 males and 75 females) in the research group. Organizational justice scale, organizational silence scale, organizational cynicism scale and job performance sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
3
16
0
4
Order By: Relevance
“…According to the result of the study, teachers' have the highest point in behavioural dimension more than emotional and cognitive dimensions. These results show similarities with the study results of Ayık [69]; Erdoğdu [70]; Polat [71]. Considering that cynicism is something undesired in organizations, it can be concluded that teachers' having moderate level of cynicism attitude can mean that there is a problem in their institution and that the teachers are not comfortable about this.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to the result of the study, teachers' have the highest point in behavioural dimension more than emotional and cognitive dimensions. These results show similarities with the study results of Ayık [69]; Erdoğdu [70]; Polat [71]. Considering that cynicism is something undesired in organizations, it can be concluded that teachers' having moderate level of cynicism attitude can mean that there is a problem in their institution and that the teachers are not comfortable about this.…”
Section: Discussionsupporting
confidence: 84%
“…This reflected teachers' beliefs about the discrepancies between what the school says and does inconsistencies between practices and deeds, and teachers' doubts about implementations in the school. In the research conducted by Erdoğdu [70], it is aimed to examine the effect of organizational justice behaviours on organizational silence and cynicism regarding the opinions of academics serving at Schools of Physical Education and Sports and Faculties of Sports Sciences. The research showed that sub-dimensions of organizational cynicism are at low levels.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational silence could even manifest as helplessness to talk about violence or abuse that is happening in workplaces. A climate of silence exists where there is injustice, which leads to fear and anxiety 15 …”
Section: Introductionmentioning
confidence: 99%
“…Justice plays a role in the systematic improvement of individual and societal life and is an important component of organizations where an individual spends a large part of his or her daily life in the organization. [2] Justice is perceived as an activity or choice that is known to be ethically right keeping in mind moral, religious, equality, and equity. [3] Organizational justice is considered as an important incentive for organizational behavior and refers to the perception of individuals and groups regarding fair treatment that they received from the organization and fairness in the distribution of resources and opportunities, wages, decision-making processes, interpersonal behaviors and provision of information within their work environment.…”
Section: Introductionmentioning
confidence: 99%